Applications of Simulation-Based Methods in Finance: The Use of ModelRisk Software - HABIBI, Hamed; HABIBI, Reza (Journal of Advanced Studies in Finance, 2016)
This paper has two parts. The first part considers the statistical arbitrage detection using the simulation-based approaches. The statistical arbitrage is the opportunity of attaining gain at future with a high probability with zero investment at the current time. Simulated methods relies on the direct use of three famous theorems in the field of stochastic process, namely (i) the arc-sine laws, (ii) the first passage of time, and (iii) optional sampling theorem. It is very important for investors to use the simulated approaches by user-friendly software like the ModelRisk of Excel which is done in this note. In the second part, the conditional NPVaR (CNPVaR) of a cash flow stream in the presence of exchange rate risk. The distribution of risk factors are assumed to be a specified location-scale distribution. The application of dynamic programming and quadratic programming are studied.
Keywords: arc-sine laws; CNPVaR; dynamic and quadratic programming; exchange rate risk; first passage of time; optional sampling theorem; statistical arbitrage